Altered recruitment of Sp isoforms to HIV-1 long terminal repeat between differentiated monoblastic cell lines and primary monocyte-derived macrophages - McAllister, John J.; Dahiya, Satinder; Berman, Rachel; Collins, Mackenzie; Nonnemacher, Michael R.; Burdo, Tricia H.; Wigdahl, Brian (Frontiers in Virology, 2022)
Human immunodeficiency virus type 1 (HIV-1) transcription in cells of the monocyte-macrophage lineage is regulated by interactions between the HIV-1 long terminal repeat (LTR) and a variety of host cell and viral proteins. Binding of the Sp family of transcription factors (TFs) to the G/C box array of the LTR governs both basal as well as activated LTR-directed transcriptional activity. The effect of monocytic differentiation on Sp factor binding and transactivation was examined with respect to the HIV-1 LTR. The binding of Sp1, full-length Sp3 and truncated Sp3 to a high affinity HIV-1 Sp element was specifically investigated and results showed that Sp1 binding increased relative to the binding of the sum of full-length and truncated Sp3 binding following chemically-induced monocytic differentiation in monoblastic (U-937, THP-1) and myelomonocytic (HL-60) cells. In addition, Sp binding ratios from PMA-induced cell lines were shown to more closely approximate those derived from primary monocyte-derived macrophages (MDMs) than did ratios derived from uninduced cell lines. The altered Sp binding phenotype associated with changes in the transcriptional activation mediated by the HIV-1 G/C box array. Additionally, analysis of post-translational modifications on Sp1 and Sp3 revealed a loss of phosphorylation on serine and threonine residues with chemically-induced differentiation indicating that the activity of Sp factors is additionally regulated at the level of post-translational modifications (PTMs).